SUPRATENTORIAL SPACE OCCUPYING LESION ET CAUSA IDIOPATHIC AND HYDROCEPHALUS - Amanda, Cyntia (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Space occupying lesion (SOL) is a lesion that extends or occupies space in the brain, including tumors, hematoma, and abscess. The position of SOL in the brain has a dramatic effect on the signs and symptoms. Boy, 13 years old, with a chief complaint of pain on the back of the head like a throbbing. The pain felt more intense over the past 2 weeks and occured ± 5 times a day and accompanied by vomiting. Complaints often heavier when he wake up in the morning. The blood pressure, pulse, temperature, and respiration are normal. Abnormalities were not found in the examination of the cranial nerves, brain membranes sign stimuli, motor system, sensibility, coordination, autonomic nerves, and noble function. The examination of the balance had positive results, obtained in the Romberg test. CT scan examination show the picture of hipodens mass in the posterior and ventricular IV dilation. Diagnosis of patients is supratentorial SOL et causa idiopathic and hydrocephalus. Space occupying lesion and hydrocephalus experienced by these patients is idiopathic, but we can not rule out the possibility of collision risk factors that occur while the patient is still being a child. Surgery is the best way to resolve a case like this before going further complication. [J Agromed Unila 2014; 1(2):161-165] Keywords: brain tumors, hydrocephalus, shunt, space occupying lesion